LATIHAN RENTANG GERAK PADA PASIEN PASCA STROKE DI WILAYAH KERJA PUSKESMAS BONTOMARANNU KABUPATEN GOWA: Movement Flat Training on Post Stroke Patients in Bontomarannu Puskesmas Working Area Gowa District (LPPM - STIKES Pemkab Jombang, 2020)
Stroke is a condition of neurological changes caused by disruption in blood circulation to parts of the brain that experience hemiparese if the handling is not right can cause complications functional disorders, mobilization disorders, disruption of daily activities and disabilities that can not be cured. The purpose of this activity is an evaluation of the knowledge and skills to do post-stroke range of motion exercises conducted on January 29-30, 2020 using the lecture, question and answer method and simulation of post-stroke range of motion patients. The results showed that there was a significant effect after being given a Range of Motion with a value of sig <0.05. Conclusions Most post-stroke sufferers are able to carry out Range of Motion exercises. Suggestions are needed for the support or involvement of family members so that the implementation of the Range of Motion can be carried out continuously in patients after stroke